The face of the campus press the role orientations of campus journalists during the 2025 midterm elections - Fernandez, Pilar Teresa C.; Congjuico, Teresa S. (Quezon City University of the Philippines Diliman, 2025)
This undergraduate thesis examines the role orientations of campus journalists amid the 2025 midterm elections. Campus journalists have played an integral role throughout Philippine history by providing alternative and people-oriented news during periods of political crises. In a time when disinformation and attacks against the campus press prevail, it is then important to shed light on the narratives of student journalists and their understanding of their roles. To do so, the study analyzes the perspectives of 15 campus journalists from The Philippine Collegian, The Varsitarian, and The Guidon
which were obtained through semi-structured and in-depth interviews. The study also utilizes the six journalistic professional roles to determine how campus journalists define and understand their perceived roles.
Thesis
Keywords: College student newspapers and periodicals -- Philippines; Journalism, College -- Philippines